2022
DOI: 10.3390/jcm11102732
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of Lifestyle Factors in Perpetuating Chronic Pain: Towards Precision Pain Medicine

Abstract: Chronic pain has a massive personal and socioeconomic impact and remains a challenge for many clinicians around the world [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…A recent systematic review by Young et al found that the PROMIS-Physical Function(PROMIS-PF) and PROMIS-Pain interference(PROMIS-PI) demonstrate moderate to strong correlations with the NDI, VAS, and SF-12 [68]. Additionally, there is increasing interest in lifestyle behaviors related to neck pain [69][70][71][72]. PROMs related to lifestyle behaviors such as sleep, which has been shown to contribute to neck pain intensity and outcomes, were not found within our review [72].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review by Young et al found that the PROMIS-Physical Function(PROMIS-PF) and PROMIS-Pain interference(PROMIS-PI) demonstrate moderate to strong correlations with the NDI, VAS, and SF-12 [68]. Additionally, there is increasing interest in lifestyle behaviors related to neck pain [69][70][71][72]. PROMs related to lifestyle behaviors such as sleep, which has been shown to contribute to neck pain intensity and outcomes, were not found within our review [72].…”
Section: Discussionmentioning
confidence: 99%
“…Data pertaining to an individual's daily pain levels, dietary intake, exercise and sleep patterns, and water consumption were tracked and stored using the application and through notes taken by Mymee health coaches. There is an established evidence base that supports targeting lifestyle factors such as physical activity, sleep disturbance, and weight reduction ( 17 20 ) and a growing evidence base to support targeting nutrition ( 21 24 ) in order to reduce pain levels and associated morbidity among individuals living with CNCP.…”
Section: Methodsmentioning
confidence: 99%
“…Activities that are persisted require activity pacing self-management and acceptancebased interventions (Figure 2). [54]).…”
Section: Personalizing Physical Activity and Exercise Therapy Interve...mentioning
confidence: 99%
“…Figure 2. Clinical reasoning decision-making tree for designing physical activity programs within the personalized multimodal lifestyle interventions for individuals with chronic pain (modified from[54]). …”
mentioning
confidence: 99%